2011
DOI: 10.1007/s00216-011-5281-z
|View full text |Cite
|
Sign up to set email alerts
|

Studying pigments on painted plaster in Minoan, Roman and Early Byzantine Crete. A multi-analytical technique approach

Abstract: Wall paintings spanning two millennia of Cretan painting history and technology were analysed in an effort to determine similarities and evolutions of painting materials and technology. A multi-technique approach was employed that combined the use of a) laser-induced breakdown spectroscopy (LIBS) and Raman microspectroscopy, based on mobile instrumentation, appropriate for rapid, routine-level object characterization, and b) non-destructive x-ray diffractometry (XRD), performed directly on the wall painting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…Considering that paints can be significantly heterogeneous, careful aiming of the laser beam is critical for obtaining reliable results. However, given that Raman signals in some cases turn out to be quite weak, or masked by fluorescence emission, arising from pigments, binders or impurities, it is not uncommon that Raman analysis may not be fully conclusive concerning the identity of the pigment or pigments used in a painted object [26] particularly when analysis is performed in situ.…”
Section: Methodology For In Situ Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that paints can be significantly heterogeneous, careful aiming of the laser beam is critical for obtaining reliable results. However, given that Raman signals in some cases turn out to be quite weak, or masked by fluorescence emission, arising from pigments, binders or impurities, it is not uncommon that Raman analysis may not be fully conclusive concerning the identity of the pigment or pigments used in a painted object [26] particularly when analysis is performed in situ.…”
Section: Methodology For In Situ Analysismentioning
confidence: 99%
“…Particularly, in the context of wall painting analysis, research studies by Bruder et al [25] illustrate the complementarity of LIBS and Raman microscopy for the in situ analysis of fresco replicas while Westlake et al [26] have demonstrated the combined use of the techniques in the analysis of mural painting fragments, still performing analyses on small plaster fragments in the analytical laboratory. At this stage it is noted that hybrid LIBS-Raman systems, in which the two spectroscopic techniques utilize the same pulsed laser source, spectrometer and detector, have been proposed that perform combined measurements on heritage samples.…”
Section: Introductionmentioning
confidence: 99%
“…The mobile Raman spectrometer (HE 785, Horiba-Jobin Yvon, France) was employed with excitation at 785 nm provided by a cw (continuous wave) diode laser coupled to an optical head ( [21,22]). A light-emitting diode (LED) and a high resolution colour camera (video microscope) are also part of the optical head and offer a very clear view of the area under investigation, necessary for positioning the beam on individual areas.…”
Section: Analytical Documentationmentioning
confidence: 99%
“…The mobile LIBS spectrometer (LMNTII+), developed and constructed at IESL-FORTH, was used for this study [21,22]. The instrument uses a compact passively Q-switched Nd:YAG laser emitting pulses at 1064 nm (10 mJ/ pulse, 10 ns).…”
Section: Libs Spectroscopymentioning
confidence: 99%
“…Although portable XRF systems are becoming more available, the above mentioned techniques cannot be applied for non-destructible samples of considerable or relatively big size, from museum collections, or for glass items that must be reintegrated into a work of art, as for instance, stained glass windows. Although LIBS has been used in several archaeometrical studies of different cultural heritage materials, [21][22][23][24][25][26] those devoted to historical glasses are scarce. These studies have focused on finding the optimal LIBS parameters for the analysis of model soda lime silicate 27 and historical lead silicate glasses, 28 on the characterization of chromophores and opacifiers of ancient glasses, and on degradation pathologies.…”
Section: Introductionmentioning
confidence: 99%